PENDIDIKAN LINGKUNGAN UNTUK ANAK USIA DINI PERSPEKTIF HADIS - Khoirotin Khoirotin; Awallia Romadhona; Marhumah Marhumah; Iffah Khoiriyatul Muyassaroh (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
This study explores the deep implications of Islamic teachings, particularly Hadith, as a basic framework for instilling ecological awareness in children. The main objective is to carefully analyze the Hadiths that contain ecological values and further formulate a comprehensive conceptual model for environmental education that fits the Islamic pedagogical context in early childhood. Using qualitative research methodology, the study utilizes the thematic (maudhu'i) hadith approach to systematically examine prophetic traditions related to environmental preservation, cleanliness, human responsibility as khalifah fil ardhi (leader on earth), and the imperative to maintain ecological balance. The results unequivocally show that the hadith provides a very rich ethical and spiritual foundation for fostering a deep appreciation of the environment and a sense of personal accountability for its well-being. The study proved that effective internalization of these profound hadith values is achieved through a variety of diverse and developmentally appropriate strategies including consistent habituation, role modeling, engagement in interactive and play-based activities, and building strong and synergistic collaboration between families and educational institutions.